2002
DOI: 10.1002/chin.200236013
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Phase Equilibria in the AgGaS2—GeS2 System.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…However, the small difference between the liquidus and solidus temperatures is quite important for the single crystal growth technology of the solid solution, as it permits to produce crystals with negligible composition variation along the grown crystal. As to end compositions, melting temperature determined for AgGaGeS 4 is T¼112975 K that well relates to earlier result T¼1133 K [11] and is noticeably higher the values T¼1118, 1113, and 1121 K reported in Refs. [10,14,18], respectively.…”
Section: Phase Diagram Of Aggages 4 -Aggage 3 Se 8 Systemsupporting
confidence: 81%
See 2 more Smart Citations
“…However, the small difference between the liquidus and solidus temperatures is quite important for the single crystal growth technology of the solid solution, as it permits to produce crystals with negligible composition variation along the grown crystal. As to end compositions, melting temperature determined for AgGaGeS 4 is T¼112975 K that well relates to earlier result T¼1133 K [11] and is noticeably higher the values T¼1118, 1113, and 1121 K reported in Refs. [10,14,18], respectively.…”
Section: Phase Diagram Of Aggages 4 -Aggage 3 Se 8 Systemsupporting
confidence: 81%
“…The quaternary g-phase that forms in the AgGaSe 2 -GeSe 2 system exists in the range of 65-88 mol% GeSe 2 at T ¼720 K with the melting point maximum at T¼995 K, which corresponds to the composition AgGaGe 3 Se 8 (space group Fdd2; a ¼1.2431, b¼2.3806, c ¼0.7135 nm) [13]. The crystals of AgGaGeS 4 and of the g-phase selenide were obtained by many authors and their properties were extensively reported [10][11][12][13][14][15][16][17][18][19][20][21][22]. As AgGaGeS 4 and AgGaGe 3 Se 8 are isostructural with minor differences in the ionic radii of the interchangeable elements (for a case of isovalent substitution), one can expect the formation of considerable solid solution ranges between these two compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quaternary sulphide AGGS melts congruently [13], which enables oriented crystallization when growing single crystals. At the same time, Chbani et al [14] have shown that Ag 2 S-Ga 2 S 3 -GeS 2 system in which the quaternary compound appears reveals a large region of glass formation. This indicates high viscosity of the melts of this system and, consequently, slow diffusion in the melt.…”
Section: Methodsmentioning
confidence: 94%
“…Phase equilibria in the quasi-ternary systems Ag 2 X-B III 2 X 3 -C IV X 2 (B III = Ga, In; C IV = Si, Ge, Sn; X = S, Se) were partially investigated [1][2][3][4][5]. The results show that nearly all compounds form at the AgB III X 2 -C IV X 2 sections with a 2:1 ratio for the quaternary phases Cu 2 In 2 SiS 6 (space group (SG) Cc) [6], Ag 2 In 2 SiSe 6 (SG Cc) [7], Ag 2 In 2 GeSe 6 (SG Cc) [8]; and 1:1 ratio for the phases AgGaGeS 4 (SG Fdd2) [3], AgInSnS 4 (SG Fd3m) [9], Ag 0.735 InGeSe 4 (SG P42c) [10], AgInSnSe 4 [5].…”
Section: Introductionmentioning
confidence: 99%